The potential role of vitamin D supplementation in the treatment of Dry Eye Disease (DED): a systematic review - Tiara Alexander; Eunike Cahyaningsih (DiscoverSys Inc., 2022)
Background: Dry Eye Disease (DED) is a prevalent condition that involves instability, increased osmolarity, and inflammation of the tear film and ocular surface. Vitamin D is known for its anti-inflammatory properties. Association between vitamin D deficiency and increased incidence of DED has been suggested. However, no study currently exists that systematically reviews the potential role of vitamin D as a treatment for DED. Methods: The literature search was performed on December 2021 through PubMed, Scopus, ProQuest, EBSCOhost, ScienceDirect, dan Cochrane Library using the relevant keywords. The risk of bias was assessed using the Cochrane Risk of Bias tool, ROBINS-I tools, and the Newcastle-Ottawa Scale. Results: A total of 700 articles were found, 6 of which were considered relevant based on PRISMA protocol. The included articles consist of 2 case controls, a randomized interventional study, and 3 observational studies. Vitamin D supplementation improved tear stability, symptoms of dry eye disease, and serum vitamin D level affected the efficacy of topical therapy for DED. Conclusion: Despite this beneficial finding, serum vitamin D level does not significantly correlate with DED symptoms which the multifactorial nature of the disease might cause.